ISLAMIC CORPORATE RESPONSIBILITY DAN KINERJA KEUANGAN PADA BANK UMUM SYARIAH DI INDONESIA - Cahyaningtiyas, Eka; Canggih, Clarashinta (Universitas Negeri Surabaya, 2020)
In this modern era, the company's goals have shifted. Not merely pursuing profit, but competing to create a good image in the eyes of the public and stakeholders. This study aims to examine the influence of ICSR on financial performance in Islamic commercial banks. The method in this research is quantitative with panel data analysis. Samples used was 11 Islamic commercial banks in Indonesia with a purposive sampling technique using secondary data sources from the 2016-2018 financial statements.The results show that the Islamic Corporate Social Responsibility (ICSR) negative effect on financial performance in Islamic banks.